2010
DOI: 10.1111/j.1752-8062.2010.00242.x
|View full text |Cite
|
Sign up to set email alerts
|

Variants in Genes Involved in Functional Pathways Associated with Hypertension in African Americans

Abstract: Essential hypertension (HBP) is a complex trait with a substantial heritable component. The purpose of this study was to determine if variants in the G‐protein coupled receptor Kinase‐4 (GRK4), nitric oxide synthase‐3 (NOS3), or angiotensin converting enzyme (ACE) genes are associated singly or through complex interactions, with HBP in African Americans aged 18–49 years. TaqMan Assays were used for genotyping the GRK4 and NOS3 variants. The ACE I/D variant was obtained by polymerase chain reaction and electrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…[43]. There is also a report of a negative association of the A486V SNP and hypertension in African Americans, although this study did also see some signal for hypertension with the R65L SNP, in association with NOS3 polymorphisms [44]. In contrast, studies in patients of European ancestry failed to find association with either SNP A142V or A486V [45] [46].…”
Section: Introductionmentioning
confidence: 79%
“…[43]. There is also a report of a negative association of the A486V SNP and hypertension in African Americans, although this study did also see some signal for hypertension with the R65L SNP, in association with NOS3 polymorphisms [44]. In contrast, studies in patients of European ancestry failed to find association with either SNP A142V or A486V [45] [46].…”
Section: Introductionmentioning
confidence: 79%
“…In addition to the above-mentioned human studies, no single site GRK4 polymorphism showed significant association with hypertension in a population from Ghana (275). Yet, in another study, GRK4-A486V has also been implicated with hypertension, as has R65L, but only when in conjunction with other polymorphisms (156). To clarify discrepancies, meta-analysis of all five human studies was recently conducted and subgroup analysis by ethnicity revealed that GRK4-A486V inversely correlated with hypertension among East Asians, while it positively correlates among Europeans.…”
Section: B Grk4 and Grk6 In Hypertensionmentioning
confidence: 88%
“…The first cohort included 412 young AA adults aged 18–49 years [18] and the second cohort included 300 AA youth aged 12–19 years [19]. A total of 38 AA male cases (SBP≥140 mmHg or DBP≥90 mmHg with or without medication) and 38 age (±2 years) and BMI (normal/overweight/obese) matched male controls (SBP<120 mmHg and DBP<80 mmHg) were selected from the young adult cohort and 6 AA male EH cases (SBP≥140 mmHg) and 6 age (±2 years) and BMI (normal/overweight/obese) matched controls (SBP<110 mmHg and DBP<70 mmHg) were selected from the youth cohort.…”
Section: Methodsmentioning
confidence: 99%